Analysis of active site loop amino acids of lactate dehydrogenase from Plasmodium vivax by site-directed mutagenesis studies - Turgut-Balik, Dilek; Sadak, Dilek; Celik, Venhar (Wiley, 2006)
The spread of resistance of malaria parasites to conventional chemotherapies necessitates the development of new drugs. The present study analyzes the active site loop of the enzyme lactate dehydrogenase from Plasmodium vivax (PvLDH). A five-amino acids insertion was observed in the active site loop of PvLDH, as in other plasmodial LDHs, which is absent in human LDH and is therefore a potential novel target site for new antimalarial drugs. This study describes the mutagenic testing of overproduced Plasmodium vivax lactate dehydrogenase to evaluate the importance of the inserted amino acids in the active site loop, which were previously identified as important residues by crystal structure studies. Deletion of these 5 extra amino acids in the active site loop resulted in an inactive form of the protein, supporting the notion of using this site as a novel target for antimalarial drug design.
Keywords: lactate dehydrogenase; site-directed mutagenesis; substrate specificity loop; antimalarials